What Plasma Can Tell Us When Tissue Cannot: A Case Report of Genomic Testing in mCRPC and Clinical Response to Treatment With the PARP Inhibitor Rucaparib - Petrylak, Daniel P.; Watkins, Simon P.; Loehr, Andrea (Frontiers in Oncology, 2022)
Background: The poly(ADP-ribose) polymerase (PARP) inhibitor rucaparib was approved in the United States based on the phase 2 TRITON2 study of patients with BRCA1 or BRCA2 (BRCA)–mutated metastatic castration-resistant prostate cancer (mCRPC). Although genomic screening is recommended as part of a comprehensive assessment of prostate cancer prognosis and treatment options, the best way to select patients with mCRPC for treatment with a PARP inhibitor depends on individual clinical circumstances. For example, assessment of tumor tissue may not always be feasible. Genomic testing of DNA from plasma has become more readily available, providing a minimally invasive option to evaluate DNA from primary and metastatic lesions simultaneously. Case presentation: A patient from TRITON2 with BRCA-mutated mCRPC had a response to the PARP inhibitor rucaparib and remained on treatment for 32 weeks, which was >2 times longer than the duration of each of his prior therapies (bicalutamide, docetaxel, abiraterone). The patient enrolled in TRITON2 based on results of local genomic testing of an archival biopsy that indicated the presence of a BRCA1 T1399I (allelic fraction, 19%) mutation. Local testing also identified an ATM G1663C mutation, a TP53 P191del mutation, and a BRAF K601E mutation. Analysis of a plasma sample obtained before the patient started rucaparib detected the same alterations as those in the archival biopsy, but it also revealed the presence of a BRCA2 homozygous loss (whole gene, 26 of 26 exons) and several other alterations of unknown functional impact. We hypothesize the response of the patient’s tumor to rucaparib was likely driven by DNA damage repair deficiency caused by homozygous loss of all BRCA2 exons. Following discontinuation from rucaparib due to clinical disease progression, the patient received carboplatin and cabazitaxel for ≈3 weeks. The patient died due to progression of his disease. Conclusions: A notable aspect of this case is the differences in alterations detected in the archival tumor sample and a more recent plasma sample. This highlights the advantages of plasma testing compared with tissue testing when selecting targeted therapies for treatment of mCRPC; however, physicians must determine which tool presents the best solution for each individual case.